2021
DOI: 10.1007/s40534-021-00231-4
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel measurement of aerodynamic characteristics of trains passing each other on a simply supported box girder bridge

Abstract: The aerodynamic performance of high-speed trains passing each other was investigated on a simply supported box girder bridge, with a span of 32 m, under crosswinds. The bridge and train models, modeled at a geometric scale ratio of 1:30, were used to test the aerodynamic forces of the train, with the help of a designed moving test rig in the XNJD-3 wind tunnel. The effects of wind speed, train speed, and yaw angle on the aerodynamic coefficients of the train were analyzed. The static and moving model tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Under the unsymmetrical load of 57 kN, the maximum torsion angle is 0.006 • . The maximum torsion angle is less than the value that was reported in a reference (0.019 • ), in which the torsional angle of a simple supported railway box girder was investigated [16]. Therefore, it demonstrated that the torsional stiffness of the girder tested in this study is sufficient to resist unsymmetrical loading and that the torsional deformation is not obvious.…”
Section: Torsional Performance Of the W-shaped Web Box Girdercontrasting
confidence: 47%
“…Under the unsymmetrical load of 57 kN, the maximum torsion angle is 0.006 • . The maximum torsion angle is less than the value that was reported in a reference (0.019 • ), in which the torsional angle of a simple supported railway box girder was investigated [16]. Therefore, it demonstrated that the torsional stiffness of the girder tested in this study is sufficient to resist unsymmetrical loading and that the torsional deformation is not obvious.…”
Section: Torsional Performance Of the W-shaped Web Box Girdercontrasting
confidence: 47%
“…There is mutual aerodynamic interference between vehicles and bridges under crosswinds. Some achievements have been made in the research of aerodynamic characteristics of trains in exposed environment, such as on the ground, subgrade, viaduct, or an open bridge structure [37][38][39][40][41]. However, only a few studies have been carried out on the aerodynamic interference effects of complex bridge structures (such as truss girder bridge) on trains.…”
Section: Bridge Deck Modelmentioning
confidence: 99%
“…The traditional test method mainly adopts the static vehicle model wind tunnel test, in which the force is measured by the balance. Recently, the moving train model test was used in several studies [30,31] to compare with the static train model test. The results show that the aerodynamic coefficients obtained by the two test methods are different.…”
Section: Static Wind Loadsmentioning
confidence: 99%
“…The final curve can also be synthesized by testing the aerodynamic coefficients of train at different positions. Second, static-dynamic intersection, usually the train on the windward side or leeward side is in a stationary state [31]. Third, dynamic intersection, both trains on the windward side and leeward side are in motion [41].…”
Section: Sudden Change Effect Of Windsmentioning
confidence: 99%